Stunted and ferritin levels in children aged 0-24 months: Does gender influence the incidence? - Widjaja, Nur Aisiyah; Atmaja, Ni Made Indah Dwijayanti; Irawan, Roedi; Hanindita, Meta Herdiana; Ardianah, Eva (Progress in Nutrition, 2024)
Background and aim: Stunting is still a global nutritional problem in developing countries such as Indonesia. Iron deficiency occurs in the stunting population due to the depletion of iron stored and stimulates hypoxia in hepatic cells which lead to the inhibition of protein synthesis, including IGF-1. Serum ferritin, the stored form of iron, is a sensitive marker for iron storage detection. This study was conducted to access growth faltering, stunting, and ferritin levels in children under 2 years old.Methods: A cross-sectional study was performed using secondary data taken from medical records of children aged under 2 years old who were visiting Nutrition and Metabolic Diseases doctors in outpatients of Husada Utama Hospital from July 2018 until June 2020. All data were analyzed using SPSS ver. 21.0 (IBM, UK), including the test of normality and homogeneity, independent sample T-test (or Mann-Whitney U Test), Chi-square test, and Fischer exact. Bivariate analysis was conducted to determine the relationship between variables.Results: 44.83% (52 subjects) were undernourished. The incidence of stunted/severely stunted was more frequent in males than females (44.83% or 26 subjects vs. 25.86% or 15 subjects). Ferritin level was significantly lower in males than females (29.69 + 24.80 vs. 53.38 + 95.36 µg/dl, P=0.011). There was a weak negative correlation between low-level ferritin with sex (r=-0.184, P=0.048). Being male had a 2.450-fold risk of low-level ferritin (95% CI [0.994-6.042], P=0.052). For the incidence of stunted, being male had a 2.329-fold risk of stunted (95% CI [1.064-5.097], P=0.034). Stunted did not correlate with a low level of ferritin (r=0.066, P=0.478).Conclusions: There was a correlation between sex with low levels of ferritin. Males were at risk of low-level ferritin and stunted in young children aged 0-24 months old.